2009
DOI: 10.1002/ange.200901550
|View full text |Cite
|
Sign up to set email alerts
|

Microfluidic Confinement of Single Cells of Bacteria in Small Volumes Initiates High‐Density Behavior of Quorum Sensing and Growth and Reveals Its Variability

Abstract: Eine ist ein Quorum: Nur eine bis drei Zellen von Pseudomonas‐aeruginosa‐Bakterien können mithilfe der Mikrofluidik in kleinen Volumina eingegrenzt werden. Diese wenigen Zellen sind zum Quorum‐Sensing (QS) befähigt und gehen QS‐abhängiges Wachstum ein. Die Befunde ergaben auch, dass bei niedriger Zahl an Zellen das Auslösen von QS innerhalb einer Klonpopulation sehr variabel ist.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
82
1
2

Year Published

2009
2009
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(89 citation statements)
references
References 42 publications
(38 reference statements)
4
82
1
2
Order By: Relevance
“…According to Hense et al (2007), cells can indeed not distinguish between the three key determinants of autoinducer concentration, namely cell density, spatial distribution of the cells and mass-transfer properties. Because QS pathways are involved in the regulation of a number of key functions in many bacterial species, especially those associated with virulence (Fuqua & Greenberg, 2002;Reading & Sperandio, 2006), the possible cell density independent induction of QS could alter significantly the organisms' ability to thrive in a given environmental setting (Boedicker et al, 2009;Carnes et al, 2010;Connell et al, 2010). Moreover Baysse et al (2005) reported that alterations in membrane properties of P. aeruginosa resulted in premature production of C4-HSL and C6-HSL, which suggests that the QS system was also activated independently of cell density.…”
Section: F Mastroleo and Othersmentioning
confidence: 99%
“…According to Hense et al (2007), cells can indeed not distinguish between the three key determinants of autoinducer concentration, namely cell density, spatial distribution of the cells and mass-transfer properties. Because QS pathways are involved in the regulation of a number of key functions in many bacterial species, especially those associated with virulence (Fuqua & Greenberg, 2002;Reading & Sperandio, 2006), the possible cell density independent induction of QS could alter significantly the organisms' ability to thrive in a given environmental setting (Boedicker et al, 2009;Carnes et al, 2010;Connell et al, 2010). Moreover Baysse et al (2005) reported that alterations in membrane properties of P. aeruginosa resulted in premature production of C4-HSL and C6-HSL, which suggests that the QS system was also activated independently of cell density.…”
Section: F Mastroleo and Othersmentioning
confidence: 99%
“…However, the long term culture of algal cells in microdroplets is likely to result in decreased cell viability, in part due to the nutrition depletion in such small volumes (pL). Boedicker et al 26 showed that the confinement of bacteria in microdroplets can induce high-density behaviour in small populations and may be used as a general system in which secreted signal molecules regulate some fundamental biological functions. Microdroplet technology could be used to determine if similar phenomena are observed when culturing microalgae in such environments.…”
mentioning
confidence: 99%
“…In a very elegant study, Ismagilov demonstrated that quorum sensing could still be induced after confining individual cells to a small space. [18] Therefore, the conclusion was that "one is a quorum"; that is, quorum sensing is not always a collective action.…”
Section: Angewandte Chemiementioning
confidence: 98%